The factors associated with successful early enteral feeding in gastroschisis - Theerayuth Pratheeppanyapat (2018)
© 2018, Springer-Verlag GmbH Germany, part of Springer Nature. Background: Gastroschisis is the most common congenital abdominal wall defect. Due to the exposure of midgut to amniotic fluid, the recovery of bowel function is often delayed. This study aimed to identify the factors associated with the successful early enteral feeding in gastroschisis and to develop further guidelines of treatment. Methods: A retrospective cohort study of gastroschisis babies from January 2006 to December 2015 was done. Exclusion criteria were incomplete data and death. Successful early enteral feeding was defined when full feeding was achieved within 21 days of life. Results: One hundred and five gastroschisis patients were divided into a successful early-feeding group (n = 56, 53%) and a non-successful early-feeding group (n = 49, 46%). In multivariable analysis, significant factors for successful feeding clustered by primary treatment were female (RR = 1.38, P value < 0.001), gestational age > 36 weeks (RR = 1.23, P value < 0.001), age at surgery less than 10 h (RR = 1.15, P value < 0.001), postoperative extubation time < 4 days (RR = 1.39, P value < 0.001), and age when feeding started less than 10 days (RR = 35.69, P value < 0.001). Conclusion: Several factors were found to be associated with successful early enteral feeding. The modifiable factors found in this study were surgery within 10 h, early postoperative extubation within 4 days, and feeding started before 10 days of life. These will guide the management of gastroschisis to achieve successful early enteral feeding.